2001
DOI: 10.1038/ng1001-166
|View full text |Cite|
|
Sign up to set email alerts
|

A gene encoding a putative GTPase regulator is mutated in familial amyotrophic lateral sclerosis 2

Abstract: Amyotrophic lateral sclerosis 2 (ALS2) is an autosomal recessive form of juvenile ALS and has been mapped to human chromosome 2q33. Here we report the identification of two independent deletion mutations linked to ALS2 in the coding exons of the new gene ALS2. These deletion mutations result in frameshifts that generate premature stop codons. ALS2 is expressed in various tissues and cells, including neurons throughout the brain and spinal cord, and encodes a protein containing multiple domains that have homolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
392
0
6

Year Published

2003
2003
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 607 publications
(413 citation statements)
references
References 32 publications
9
392
0
6
Order By: Relevance
“…Mutations in SOD1 cause the classical form of ALS. Mutations in ALS2, which encodes the protein alsin, also give rise to a rare juvenile form of ALS [35,87], an infantile onset ascending hereditary spastic paralysis, and a form of complicated hereditary spastic paraplegia [11,16]. All mutations in ALS2, identified to date are missense mutations that result in unstable truncated alsin proteins implying that loss of alsin function induces the disease phenotypes [35,87].…”
Section: Alsinmentioning
confidence: 99%
“…Mutations in SOD1 cause the classical form of ALS. Mutations in ALS2, which encodes the protein alsin, also give rise to a rare juvenile form of ALS [35,87], an infantile onset ascending hereditary spastic paralysis, and a form of complicated hereditary spastic paraplegia [11,16]. All mutations in ALS2, identified to date are missense mutations that result in unstable truncated alsin proteins implying that loss of alsin function induces the disease phenotypes [35,87].…”
Section: Alsinmentioning
confidence: 99%
“…Mutations in the gene encoding Cu/Zn superoxide dismutase (SOD1) cause motor neuron degeneration through a gain of toxic property [2]. Recently, mutations in a second ALS-related gene (ALS2) were identified that cause a rare recessive form of juvenile onset ALS [5,9]. Previously, we and others have generated ALS2 knockout (ALS2 −/− ) mice that failed to display any obvious motor neuron degeneration [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…The second identified FALS-linked gene, a FALS-linked mutation of which results in an autosomal-recessive phenotype, encodes a protein named alsin. 6,7 Loss of alsin function, caused by a FALSlinked mutation, leads to the abnormal endolysosomal trafficking and contributes to motor neuron death. 8 We have independently shown that wild-type alsin suppresses mutant SOD1-induced neuronal cell death by activating a prosurvival pathway involving Rac1, PI3K and Akt3, and that FALS-linked mutations in the gene abolish the alsin function.…”
mentioning
confidence: 99%